Enhancement of perovskite-based solar cells employing core-shell metal nanoparticles. - Zhang, W; Saliba, M; Stranks, S; Sun, Y; Shi, X; Wiesner, U; Snaith, H (2013)
Recently, inorganic and hybrid light absorbers such as quantum dots and organometal halide perovskites have been studied and applied in fabricating thin-film photovoltaic devices because of their low-cost and potential for high efficiency. Further boosting the performance of solution processed thin-film solar cells without detrimentally increasing the complexity of the device architecture is critically important for commercialization. Here, we demonstrate photocurrent and efficiency enhancement in meso-superstructured organometal halide perovskite solar cells incorporating core-shell Au@SiO2 nanoparticles (NPs) delivering a device efficiency of up to 11.4%. We attribute the origin of enhanced photocurrent to a previously unobserved and unexpected mechanism of reduced exciton binding energy with the incorporation of the metal nanoparticles, rather than enhanced light absorption. Our findings represent a new aspect and lever for the application of metal nanoparticles in photovoltaics and could lead to facile tuning of exciton binding energies in perovskite semiconductors.